Рекодифікації цивільного законодавства в контексті інтеграції України у правовий простір ЄС - Харитонов, Євген Олегович; Харитонов, Є. О.; Kharytonov, Yevhen O.; Харитонова, Олена Іванівна; Харитонова, О. І.; Kharytonova, Olena I. (Херсон : Видавничий дім «Гельветика», 2019)
У статті розглядаються питання визначення значення рекодифікацій для адаптації правової системи України до європейського права. Зроблено висновок про те, що має йтися про адаптацію вітчизняного концепту права до концепту права європейського з врахуванням належності України до «цивілізацій фронтиру». Зауважено, що таку адаптацію цивільного законодавства України до права ЄС доцільно проводити у формі, так званої «рекодифікації», котра дозволяє ефективно удосконалювати чинне законодавство на підґрунті чинної концепції правового регулювання. При цьому має бути врахована та обставина, що у цивілізаціях фронтиру концепт приватного права може мати особливості, які залежать від національних системи цінностей, ментальності тощо.

The article discusses the issues of determining the significance of reсodifications to adapt the legal system of Ukraine to European law. It is concluded that we should talk about adapting the domestic concept of law to the concept of Euro - pean law, taking into account Ukraine’s belonging to the “civilization of the frontier”. It is noted that it is advisable to carry out such an adaptation of the civil legislation of Ukraine to EU law in the form of the so-called “reсodification”, which allows to effectively improve the current legislation on the basis of the current concept of legal regulation. In this case, the fact that in frontier civilizations the concept of private law may have features that depend on the national system of values, mentality and the like. The article notes that the Civil Code of Ukraine can be attributed to acts of «passion - ate type». This is due to the fact that it was created on a new conceptual basis as a code of civil society, the rule of law and a code of private law, taking into account modern European trends and experience in the development of legal systems. The “passionarity” of the Civil Code of Ukraine gives grounds for the assumption that problems in the legal regulation of civil relations can be quite easily eliminated in the future by recodification, since there is a necessary conceptual basis for this. Since the Civil Code of Ukraine, being in its essence a code of private law at the level of the concept of civil law, reflects a synthesis of Western and Eastern European traditions of law, this gives grounds for hopes for the successful adaptation of its norms to the concept of European private law, principles and certain provisions of legislative acts, which provide the legal functioning of the EU internal market. However, there is no need for a radical revision of the Civil Code of Ukraine. As a response to the challenges of our time, recodification is enough to adapt civil law to the modern concept of private law, reflected in the Draft Common Frame of Reference (DCFR). At the same time, it should be noted that adaptation to the solutions recommended by DCFR in this area can be quite complicated and will require not only the recodification of domestic legislation, but also the corresponding adaptation of legal awareness.
Харитонов Є. О. Рекодифікації цивільного законодавства в контексті інтеграції України у правовий простір ЄС / Є. О. Харитонов, О. І. Харитонова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 34. – С. 6-10.
Keywords: приватне право; цивільне законодавство; адаптація; рекодифікація; концепт; правова система; європейське право; правосвідомість; private law; civil law; adaptation; recodification; concept; legal system; European law; legal awareness; Research Subject Categories::LAW/JURISPRUDENCE